Management of Anaesthesia for a High-Risk Aerosol-Generating Procedure in a Paediatric Patient with COVID-19. (23rd March 2021) - Giwangkancana, Gezy; Oktaliansyah, Ezra; Hardianti Saputri, R. Ayu
Abstract : Introduction . Paediatric patients represent a small portion of the COVID-19 disease population. Nevertheless, the possibility of a paediatric patient requiring surgery, especially high-risk aerosol-generating surgery on the airway, while having the SARS-CoV-2 infection may potentially result in problems during the perioperative period due to concerns regarding patient, family, and staff safety. When unplanned and unrehearsed, this scenario may cause delays and efficiency issues. Our aim is to report on an 8-year-old patient with a foreign object lodged in the oesophagus with COVID-19 that required emergency surgery. Case Report . An 8-year-old female patient came to the emergency room with a history of difficulty in swallowing for 12 hours before admission, having accidentally swallowed a metal coin while playing. She did not have any recent history of disease, but her parents had noticed that, for the previous 4 days, she had had a mild fever and dry cough. Her parents and other relatives in the house had no similar complaints, and they assured us they had not been in contact with any suspected or confirmed COVID-19 patients. Our goal was to create a safe paediatric anaesthesia environment with safe working conditions for the surgical team. In this case report, we will describe our approach to patient transport, parental presence, preventions of aerosol risk, personal protection, the anaesthesia induction technique, and postoperative management. Conclusion . Safe paediatric anaesthesia, especially in a high-risk aerosol-generating procedure, during the COVID-19 era requires consideration and preparation of both the patient and healthcare provider. Multidisciplinary team work with an emphasis on a systematic and planned approach is required to improve efficiency.